THE IMPORTANCE OF THE HOST COUNTRY AND ITS REGION DEVELOPMENT STRATEGY IN CONDITIONS OF MASS MIGRATION (International Journal of Innovative Technologies in Economy, 2023)
The article deals with the main problems generated by migration processes. The causes of the migration crisis and current migration features are indicated. The necessity of migration processes managing aimed at migrants’ integration acceleration into the host society is empathized. The need of general migration strategy for the EU countries updating and the development strategies for recipient countries formation, taking to account the increase in labor resources, is substantiated. On a specific example, an analysis of the opportunities and risks associated with the implementation of a development strategy in the context of the massive influx of forced migrants (refugees) was carried out. The most expedient strategy of for the development of the country, focused on the efficient use of labor potential, has been formulated, its main tasks and key challenges, and the expectations of stakeholders have been identified. The expediency of developing a development strategy is justified by the expected results from its implementation, corresponding to the evolution of the needs of the country’s economy.